An Overview of Alternative Currency: The Bitcoin - Bhattacharjee, Sandeep; Kaur, Harmeet (Indian Journal of Finance, 2015)
The financial market is based on the currency and the volume of trade between different individuals, groups, or organizations. This trade is ruled or governed by several protocols, which limits the over flooding or inappropriations in the exchange markets. One such virtual currency that is becoming popular among users is Bitcoin. In this paper, we discussed the evolution of Bitcoin as a currency, situations preceding and aftermath, as well as its consequences and effects on the present economy. We also discussed its growth, transaction volumes, currency acceptability, and factors involved. In this paper, we have tried to ensemble related thoughts for seeking new ideas for developing an alternative financial system. The results attained thereof could give new hopes to both consumers and markets seeking more freedom in terms of volume, payment methods, anonymity, and so forth.